2022
DOI: 10.3389/fphar.2022.879745
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Gut Microbiota—Gut—Brain Axis in Perioperative Neurocognitive Dysfunction

Abstract: With the aging of the world population and advances in medical and health technology, more and more elderly patients are undergoing anesthesia and surgery, and perioperative neurocognitive dysfunction (PND) is receiving increasing attention. The latest definition of PND, published simultaneously in November 2018 in 6 leading journals in the field of anesthesiology, clarifies that PND includes preoperatively cognitive impairment, postoperative delirium, delayed neurocognitive recovery, and postoperative cogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 92 publications
0
18
0
Order By: Relevance
“…It is now thought that neurotransmitter dysfunction, neuroinflammation, oxidative stress, and mitochondrial dysfunction might play an important role in its pathogenesis. 2 , 3 , 4 , 5 Drp1 could mediate mitochondrial fission and be crucial for maintaining the stability and quality control of mitochondrial function. 23 As an organ with high oxygen consumption, brain tissue function is highly dependent on the proper functioning of mitochondria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now thought that neurotransmitter dysfunction, neuroinflammation, oxidative stress, and mitochondrial dysfunction might play an important role in its pathogenesis. 2 , 3 , 4 , 5 Drp1 could mediate mitochondrial fission and be crucial for maintaining the stability and quality control of mitochondrial function. 23 As an organ with high oxygen consumption, brain tissue function is highly dependent on the proper functioning of mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“… 1 As a multi‐disease model, neuroinflammation, neurotransmitter dysfunction, mitochondrial dysfunction, and oxidative stress are currently considered significant pathogenic PND processes. 2 , 3 , 4 , 5 However, the exact pathogenesis has not been fully elucidated, and further research is needed.…”
Section: Introductionmentioning
confidence: 99%
“…This community plays a crucial role in human health, influencing various physiological processes, including immunity, metabolism, and brain function ( 8 10 ). Recent studies have suggested that the gut microbiome may play a role in the development of PND by disrupting the gut-brain axis, which is the communication pathway between the gut and the central nervous system ( 11 , 12 ). The gut microbiome is known to be sensitive to changes in the environment, such as surgery and the administration of antibiotics, which can alter the composition and function of the gut microbiome ( 13 , 14 ).…”
Section: Dysbiosis Of Gut Microbiota In Patients With Pndmentioning
confidence: 99%
“…17 The intestinal microbiota affects neurological, endocrine, and immunological networks through the gut-brain axis, which is the bilateral communication between the central and enteric nervous systems. 18,19 Recent study reveals that the gut microbiome plays a role in anxiety and depression-like behavior, 20 and clinical research indicates that these disease situations are characterized by an abundance of pro-inflammatory and short-chain fatty acid (SCFA) producing bacterial species. 21 This pathophysiology illustrates that dysbiosis may have either positive or negative consequences on the host’s inflammatory condition.…”
Section: Introductionmentioning
confidence: 99%
“…The diverse population of the gastrointestinal (GI) microbes engages in a mutually beneficial relationship with the host. These gut microbiota affects neurological, endocrine, and immunological networks through the gut-brain axis and the bilateral communication between the central and enteric nerve systems (14, 15). A mice model shown that the genus Bifidobacterium has an antidepressant effect that is partially mediated by microbiome regulation (16).…”
Section: Introductionmentioning
confidence: 99%